Modeling information flow in the supply chain of structural steel components - Akcay, Emre Caner; Ergan, Semiha; Arditi, David (Journal of Civil Engineering and Management, 2017)
Accessing the required information in the supply chain of structural steel components is critical for minimizing costly reworks and delays. This paper identifies the information items generated in the different phases of the supply chain related to structural steel components and formalizes the process of producing and using this information. Precise details about different features of the components (e.g., their geometry and weight, connection details, cutting/bending/ punching requirements, and the type and grade of the material) are set in the various tasks performed in the different phases of the supply chain. Regardless of whether one uses paper-based systems or advanced technologies such as smart tags and radio-frequency identification (RFID), a better understanding is achieved of the processes through which a structural steel component passes. The results of this research can be used to streamline the information flow in the supply chain of structural steel components, regardless of the type of tracking technology used, hence reducing delays and reworks.